Literature Survey of SAR Algorithm in Photovoltaic System - Nithin T Abraham; K Vinoth Kumar; Vicky Jose; Dona Maria Mathew; S Suresh Kumar (International Journal of Electrical and Computer Engineering (IJECE), 2014)
Every solar energy harvester systems have got two sources of energy loss: the MPPT circuit and the dc–dc converter. To increase the efficiency of the PV energy harvester, the energy losses from the MPPT circuit and the dc–dc converter need to be minimized. Here a new MPPT algorithm called successive approximation register is introduced. This MPPT algorithm has got a power down mode and a fast tracking time, to achieve low power consumption and energy savings. With this MPPT algorithm energy losses from the MPPT circuit can be minimized and this technique can be greatly applicable to low power application systems mainly as well as for high power application.DOI:http://dx.doi.org/10.11591/ijece.v4i2.4557